Model Sistem Pengering Tenaga Surya Berbasis IoT dengan ESP32 dan DHT-11 - Gogor Christmass Setyawan; Leonard Joseph Setyawan (STMIK Banjarbaru, 2025)
This study examines the development of a solar-powered drying system that integrates Internet of Things technology to increase the efficiency of drying agricultural products. The problems faced by small farmers, especially related to inefficiencies in drying methods, are the background for this research. The main objective is to design and implement a system that uses an ESP32 microcontroller and a DHT-11 sensor for real-time temperature and humidity monitoring. The applied methodology includes system design, prototype testing, and data analysis from field experiments. The results show that this system can increase drying efficiency by up to 30% compared to traditional methods. These findings confirm that the application of IoT technology in drying systems not only offers technical solutions, but also contributes to the welfare of small farmers by reducing post-harvest losses.Keywords: Solar dryer system; Internet of Things; Drying efficiency; Small farmers; Reduction of post-harvest losses. AbstrakStudi ini meneliti pengembangan sistem pengering tenaga surya yang mengintegrasikan teknologi Internet of Things untuk meningkatkan efisiensi pengeringan hasil pertanian. Permasalahan yang dihadapi petani kecil, terutama terkait ketidakefisienan dalam metode pengeringan, menjadi latar belakang penelitian ini. Tujuan utama adalah merancang dan menerapkan sistem yang menggunakan mikrokontroler ESP32 dan sensor DHT-11 untuk pemantauan suhu dan kelembapan secara real-time. Metodologi yang diterapkan mencakup desain sistem, pengujian prototipe, dan analisis data dari eksperimen lapangan. Hasil menunjukkan bahwa sistem ini dapat meningkatkan efisiensi pengeringan hingga 30% dibandingkan metode tradisional. Temuan ini menegaskan bahwa penerapan teknologi IoT dalam sistem pengeringan tidak hanya menawarkan solusi teknis, tetapi juga berkontribusi pada kesejahteraan petani kecil dengan mengurangi kerugian pascapanen.Kata kunci: Sistem pengering tenaga surya; Internet of Things; Efisiensi pengeringan; Petani kecil; Pengurangan kerugian pascapanen